Influencing factors for Malaysian Muslim women consumers in purchasing of non-certified halal international brand makeup products in Mid Valley Megamall Kuala Lumpur - Idris, Nor Awanis; Jamaludin, Mohammad Aizat; Hazahari, Noor Yuslida; Kartika, Betania (HH Publisher, 2020)
Malaysia is expected to witness a greater demand for halal products due to increasing awareness of Islamic practices among the citizen. Malaysian Muslim women consumers spend more on cosmetics especially on those makeup products by international brands. For a Muslim, it is an obligatory to practice using only halal cosmetics for makeup products. Unfortunately, the halal awareness of non-food (cosmetics) is lacking among the consumers as compared to food products. This reason being that food is considered as consumable goods, while cosmetic is to be used on face and body; for external application and nothing internal. The main issue surrounding this strict practice (makeup products on face and body) concerns on the source of ingredients, either from halal or haram source. Ingredients sourced from haram materials will nullify the daily prayers of a Muslim. A study has shown that the customer’s intent to purchase cosmetic with non-certified halal is without a doubt if the halal products are not made available in the market. This eventuates to the infrequent use of halal logo by companies that produce makeup products and existing incidents of fraudulent pertaining to the halal logo in the market. Thus, the purpose of this study is to identify the factor influencing Malaysian Muslim women in purchasing of non-certified halal international brand makeup products. This study applied a qualitative approach based on library study and face-to-face interview with 20 Malaysian Muslim women consumers. The interview was recorded, transcribed, and applied to a content analysis. As a result, the findings demonstrated that the factor influencing Malaysian Muslim women in purchasing of non-certified halal international brand makeup products are divided into two, which are the (i) internal and (ii) external factors. Internal factors include quality, trust, brand, loyalty, price, effectiveness, safety, confidence, variety, and ingredients while external factors derived from the influencers such as makeup artists, internet celebrity, public figures, well-known entrepreneurs, bloggers, and Instagram-famous figure.